Pengaruh Pelatihan Kerja On The Job Training Terhadap Kinerja Karyawan Pada PT Radio Suara Pesona Indah Palembang - Ramli, M. Rafli Rif’at; Karimudin, Yos; Siregar, Lina Dameria (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of work training on the job training on employee performance at PT Radio Suara Pesona Indah of the City of Palembang. This research uses quantitative methods. The population in this study were radio broadcasting employees, selected using saturated sampling, so the sample in this study was the entire population of radio broadcasting employees, totaling 39 respondents. The data collection method used in the study was obtained from a questionnaire. The analysis technique used in this study is simple linear regression analysis. Based on the results of the hypothesis analysis (t test), it was concluded that the work training on the job training had a positive and significant effect on the employee performance at PT Radio Suara Indah of the City of Palembang. Keyword: Work Training, Employee Performance.